Russia Economic Report, No. 45, May 2021 : Russia’s Economic Recovery Gathers Pace - World Bank Group (World Bank, Washington, DC, 2021)
The COVID-19 pandemic continues to disrupt activity across the world, casting wide uncertainty around GDP projections. Despite the protracted and uncertain nature of the pandemic, global GDP growth is forecast to recover to 4 percent in 2021 and to moderate to 3.8 percent in 2022 under baseline assumptions established in January 2021. The baseline recovery, however, is not sufficient to return global output to pre-pandemic projections by 2022, with levels expected to be 4.4 percent below pre-pandemic projections next year. COVID-19 has reversed hard-won gains in poverty reduction, with the pandemic expected to push over 100 million people into extreme poverty by the end of 2021. Accompanying the rise in extreme poverty is that of food insecurity, especially in light of the steep falls in household incomes due to widespread job losses – many of which are not anticipated to be regained this year. The pandemic is expected to have longer-term scarring effects on productivity growth and potential output, as the erosion of business confidence further weakens investment and as human capital accumulation slows due to a deterioration in health outcomes, extended school closures, and prolonged unemployment. Global trade continues to recover, but with wide variations across countries and sectors. Global financing conditions remain accommodative amid ongoing vaccination drives in major economies.